Study on Characteristics of Poor Households in a Village in the Regency of Malang, East Java, Indonesia - Wisadirana, Darsono (Technium Social Sciences Journal, 2021)
This research looks to study the issues regarding the characteristics and the structure of poverty in households in a village, factors causing the poverty in rural households, how poverty in rural households are generally patterned and how strategies addressed to this poverty countermeasure are formulated. This research aims to describe and analyze the nature of household poverty in a village, contributing factors to it, patterns of household poverty in a village, and to formulate model employed to present countermeasure to the poverty in rural households. This research expects to gain data and information on the characteristics of poverty in rural households, the factors causing it, the patterns of rural poverty and the strategies aimed to prevent the poverty. The fundamentals of theories used in this research involve poverty web, and poverty trap (Chambers, 1983), poverty line by Sayogyo (1976), and poverty patterns and social gaps (Soemarjan, 1976). The research methods required a survey with qualitative approach. Samples were taken from two villages in the District of Kromengan, the Regency of Malang based on purposive sampling technique. The respondents were taken randomly since all households in the samples were categorized as poor, meaning all respondents had equal probabilities to be taken as samples. There were 44 samples of households. The data was collected from questionnaire, in-depth interviews in reference to interview guide, observation, and documentation. Instrument validity checking was performed by employing Pearson square correlation, while the validity of the data was assessed by means of the triangulation of sources. The data was further analyzed based on descriptive and explanative method by employing cross tabulation (crosstabs). The analysis covered individuals and the members of public or households. The research results reveal that the nature of the poverty in rural households is patterned in the structure of the following levels 1) the poorest, 2) very poor, 3) poor, and there are five contributing factors to the poverty, 1) community levies that augment residents’ expenses, 2) aggravating loans; 3) increasing cost for primary needs, 4) poor education and skills, and 5) low income. The nature of the poverty in rural households follow these patterns, 1) individual poverty, indicated by individuals’ ill-health; 2) relative poverty, indicated by affordable housing, 3) structural poverty, indicated by issues in starting up a business; 4) cultural poverty, indicated by poor skills and lack of motivation to utilize local raw materials; 5) poverty as a trend, indicated by the tendency of accepting this deprivation, where the residents believe that being poor is destined.